Inflammation and LPS-Binding Protein Enable the Stimulatory Effect of Endotoxin on Prolactin Secretion in the Ovine Anterior Pituitary: Ex Vivo Study. (14th August 2018) - Tomaszewska-Zaremba, Dorota; Haziak, Karolina; Tomczyk, Monika; Herman, Andrzej P.
Abstract : Prolactin is a hormone that plays an important role in the regulation of many physiological processes including lactation, reproduction, fat metabolism, and immune response. The secretion of prolactin could be disturbed by an immune stress commonly accompanying infection. This study was designed to determine the influence of bacterial endotoxin—lipopolysaccharide (LPS)—on prolactin gene (PRL) expression and prolactin release from the ovine anterior pituitary (AP) explants collected from saline- and LPS-treated ewes in the follicular phase. The expressions of toll-like receptor 4 (TLR4) and proinflammatory cytokines interleukin- (IL-) 1 β, IL-6, and tumor necrosis factor- (TNF-) α genes were also assayed. The results of the study showed that LPS stimulates prolactin secretion and IL-6 gene expression in the AP explants, but its action on lactotrophs depends on the immunological status of animal. It was demonstrated that an important role in enhancing the effect of LPS on the pituitary in the saline-treated ewes is played by LPS-binding protein (LBP)- "adapter molecule" for LPS binding to the cell surface receptor CD14 and then to TLR4. Also, it was found that bacterial endotoxin acting on the anterior pituitary cells may enhance prolactin secretion, and this effect of LPS could be mediated by IL-6 which is known as prolactin-releasing factor. Identification of the neuroendocrine and immune interactions in the regulation of prolactin secretion could be helpful in developing newer and more effective treatments for dysfunctions connected with disorders in this hormone secretion.